1999
DOI: 10.2307/2656970
|View full text |Cite
|
Sign up to set email alerts
|

Development of photosystem‐II activity during irradiance of etiolated Helianthus (Asteraceae) seedlings

Abstract: Light-induced development of photosystem (PS)-II activity was followed during irradiance of etiolated Helianthus annuus (sunflower) cotyledons using chlorophyll a fluorescence. Cotyledons from seedlings grown in continuous darkness for 6 d were exposed to 100 μmol photons·m(-2)·s(-1) for time periods of 1, 3, 6, and 12 h. Associated with increased time of irradiance exposure were significant: (1) increases in concentration of PS II, (2) increases in quantum efficiency of PS II, (3) decreases in the ratio of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 74 publications
1
26
1
Order By: Relevance
“…However, other physiological parameters indicated that chloroplasts were not completely mature. In particular, the maximum value for the F v /F m ratio (approximately 0.6) was lower than the one (0.83) determined for healthy and mature chloroplasts of green leaves (Björkman and Demmig, 1987), suggesting the presence of nonreducing Q B PSII complexes in the thylakoid membranes due to slow activation and/or slow development of the oxygen-evolving complex (Lebkuecher et al, 1999). Additionally, the chlorophyll a/b ratio was higher (approximately 3.8) than the same ratio (3.5) for mature chloroplasts of many higher plants.…”
Section: Functioning Of Chloroplasts In Acsccontrasting
confidence: 56%
“…However, other physiological parameters indicated that chloroplasts were not completely mature. In particular, the maximum value for the F v /F m ratio (approximately 0.6) was lower than the one (0.83) determined for healthy and mature chloroplasts of green leaves (Björkman and Demmig, 1987), suggesting the presence of nonreducing Q B PSII complexes in the thylakoid membranes due to slow activation and/or slow development of the oxygen-evolving complex (Lebkuecher et al, 1999). Additionally, the chlorophyll a/b ratio was higher (approximately 3.8) than the same ratio (3.5) for mature chloroplasts of many higher plants.…”
Section: Functioning Of Chloroplasts In Acsccontrasting
confidence: 56%
“…Thus, we suppose that leaf area expansion process also involved the synthesis and assembly of photosynthetic apparatus in Jerusalem artichoke. So far, it is not definite whether primary photochemical reaction of PSII is the limiting step of photosynthetic capacity during the leaf growth, as contradictory results have been reported in different plants (Lebkuecher et al 1999;Srivastava et al 1999;Choinski et al 2003;Jiang et al 2005Jiang et al , 2006c. These contradictory results can be attributed to the inconsistent culture protocol or plant species.…”
Section: Discussionmentioning
confidence: 68%
“…Photosystem 2 (PS2) is one of the major protein complexes in the photosynthetic apparatus in higher plants. As a result, more and more research effort has been devoted to understanding development of PS2 complex in the expanding leaves (Guenther and Melis 1990, Lebkuecher et al 1999, Srivastava et al 1999, Choinski et al 2003) and a lot of progress has been made in this field. Guenther and Melis (1990) found different developmental status of PS2 complex at various stages of chloroplast maturity.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, Choinski et al (2003) noticed that the maximal quantum yield of PS2 (φ PS2 ) increases during leaf growth. Most previous investigations, however, were focused primarily on plants growing under artificial conditions with suboptimal irradiance levels (Guenther and Melis ---1990, Lebkuecher et al 1999, Srivastava et al 1999. The development of PS2 in leaves grown under field conditions has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%